Integrated Productive Waqf Framework: Strengthening The Synergy Between Commercial Finance and Islamic Social Finance for Sustainable Economic Development - Muhamad Turmudi; Sarehan Sulong (Islamiconomic : Jurnal Ekonomi Islam, 2026)
Productive waqf has increasingly been recognized as a strategic instrument for promoting sustainable socio-economic development and strengthening the role of Islamic finance. However, its implementation remains constrained by fragmented financing mechanisms and limited integration between commercial finance and Islamic social finance. This study aims to develop a conceptual framework that explains how the synergy between these financing mechanisms can enhance the sustainability and effectiveness of productive waqf. Employing a qualitative library research approach with conceptual analysis, this study critically reviews and synthesizes contemporary literature, institutional reports, and relevant regulatory frameworks on productive waqf, Islamic social finance, commercial finance, and sustainable Islamic economic development. The analysis demonstrates that productive waqf can generate greater socio-economic impact when Islamic banks, waqf institutions, Islamic social finance organizations, regulators, and other stakeholders collaborate within an integrated governance ecosystem. Based on this synthesis, the study proposes the Integrated Productive Waqf Framework (IPWF), which integrates commercial finance, Islamic social finance, governance mechanisms, stakeholder collaboration, and sustainable development objectives into a unified conceptual model. The proposed framework contributes to the advancement of Islamic economics by providing a comprehensive perspective for strengthening productive waqf governance and offering practical insights for policymakers, Islamic financial institutions, and waqf managers in optimizing the role of waqf in sustainable economic development.